Association of clinical factors with postoperative complications of esophageal atresia - Besendörfer, Manuel; Müller, Hanna; Weiss, Christel; Wagner, Alexandra; Schellerer, Vera; Hörning, André; Diez, Sonja (Pediatrics and Neonatology, 2020)
Background: Esophageal atresia (EA) with or without tracheoesophageal fistula (TEF) remains one of the most common gastrointestinal neonatal malformations. Even though postoperative management is standardized, it differs between hospitals and disease-associated clinical factors that may play a role in outcome have not yet been assessed in detail. Methods: In this monocentric retrospective study, data of 43 patients with EA between 2010 and 2018 were analyzed. Analysis includes assessment of the clinical background, surgical technique, postoperative management including application of continuous muscle relaxation (CMR), influence of coagulation parameters such as factor XIII and incidence of complications. Results: 21 patients (49%) were preterm infants with birth weights between 490 and 2840 g (median 1893 g). Only 35% (n = 15) presented without any concomitant malformations. Within the entire study population, representing Vogt II, IIIb and IIIc, we observed an association between the development of a postoperative pneumothorax and anastomotic failure (AF) (p = 0.0013). Furthermore, pneumothorax was associated with anastomotic stenosis (AS) in Vogt IIIb patients (p = 0.0129). CMR (applied since March 2017 in 7 patients in an attempt to prevent anastomotic problems due to high complication rates) and coagulation factor XIII did not significantly correlate with postoperative outcome. Conclusion: Appearance of pneumothorax was correlated with postoperative complications. These children should be monitored carefully in closer scheduled gastroenterological follow-up esophago-gastro-duodenoscopies. CMR and factor XIII substitution did not reduce anastomotic leakage but should be tested within an enlarged study population.
CRIS-Team Scopus Importer:2020-10-23
Keywords: continuous muscle relaxation; esophageal surgery; neonatal surgery; pneumothorax; postoperative relaxation